Retroperitoneal ganglioneuroblastoma presenting as chronic diarrhea and refractory hypokalemia in a child - Venkateswari Ramesh; Janani Sankar; Geetha Jayapathy; Mahitha Velusamy (Indian Journal of Medical and Paediatric Oncology)
Neuroblastoma is the most common extracranial solid tumor in children. Neuroblastoma presenting with diarrhea as the predominant symptom is rare and can be a diagnostic challenge to the paediatrician. We present a twenty months old child with Retroperitoneal Ganglioneuroblastoma who presented with chronic diarrhea and refractory hypokalemia. Tumor removal resulted in cessation of diarrhea and correction of hypokalemia.